METHODS OF TEACHING ENGLISH FOR YOUNG PEOPLE - Jumayeva Dilbar (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Learning English will open up many opportunities for people in the future and will be invaluable for their future careers. However, teaching English to children is not an easy task. But it's not difficult if we already know how to do it This article addresses the following topics: what are the principles of teaching English to children, what are the characteristics of a language teacher, why do we teach children a foreign language, the social and psychological preparation of teachers, the emotional level and physical aspects of young students, the main roles of teachers in the classroom, and finally some practical tips and teaching techniques for beginner teachers of English. In this study is investigated teachers should experience how to teach young learners in different ways and by using methods at primary school..Furthermore, in this article is given that what kind of techniques, methods and activities are essential to teach easily for primary schools.